The Cybersecurity Playbook : How Every Leader and Employee Can Contribute to a Culture of Security - Cerra, Allison (2019)
"Today's headlines are littered with cybersecurity breaches -- each more damning than the last. For too long, cybersecurity has been relegated to the corridors of IT. Every organization's weakest link in cybersecurity is its own employees, as hackers dupe them to get access to an organization's systems. Yet most employees have no idea how to help prevent attacks, why they should bother, or what to look for. But, with any manager or employee the next unsuspecting dupe, cybersecurity can no longer be someone else's problem, but the mandate of all. While many books serve as educational resources on the topic of cybersecurity, they stop short of explaining how employees take up arms in the fight against a pernicious threat. Doing so requires demystifying cybersecurity for the business audience, giving practical prescription to these users on how they can adopt smart cybersecurity habits in their function. To make the topic both accessible and practical, this book will move beyond simply identifying the problem and provide practical prescriptions, offering simple checklists and action plans than any manager in the organization can take to protect his organization from an unknown threat. Further, the book will be based on primary marketing research, including in-depth interviews among CIOs, CISOs and other functional business leaders (e.g., CMOs and CHROs) to measure the extent of the gap among these senior leaders in making cybersecurity a business priority"--
Keywords: Computer security; Computer networks -- Security measures; Corporate culture; Confidential business information -- Security measures